Use of Artificial Intelligence Applications: Friend or Threat for Indonesian Language and Literature Education Students at Singaperbangsa University of Karawang - Amal, Bahar; Khaierunnisa, Aqillah; Rahmawati, Elisa; Syifa, Naora; Dewani, Pramesvary Nazwa; Septariyani, Putri Ratih; Fauzi, Syahrul Ilham (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
This research aims to explore the impact of artificial intelligence (AI) on students of Indonesian Language and Literature Education students at Singaperbangsa Karawang University. Through a survey of Indonesian Language and Literature Education students, this study shows that AI has become a popular tool to support the learning process, but also raises concerns about excessive dependence and a decline in critical thinking skills. The results show that AI can be a valuable tool to assist students in various academic tasks, but can also pose a threat if used unwisely. Therefore, it is important for students to understand the potential and limitations of AI, and to use it in a balanced manner to achieve optimal learning outcomes.